How challenger party issue entrepreneurship and mainstream party strategies drive public issue salience: evidence from radical-right parties and the issue of immigration - Christopher J. Williams; Sophia Hunger (European Political Science Review, 2022)
When mainstream parties accommodate radical-right parties, do citizens grow more concerned about immigration? Based on a rich literature, we argue that challenger parties' ability to affect mainstream party positions, particularly on immigration, is associated with greater public salience of immigration and voter positivity towards challengers exists. We use Comparative Manifesto Project and Comparative Study of Electoral Systems data in order to show that challenger issue entrepreneurship, and mainstream accommodation are associated with greater public concern for challenger issues. These factors do not result in greater public positivity towards challengers. Our findings thus support the argument that a mainstream party accommodative strategy might not be as beneficial for them as often expected by pundit and political scientists alike. This has implications for understanding the effect of indirect party strategies on public attitudes, since mainstream accommodation changes public concern regarding issues, which may bolster challengers' positions, including radical-right parties.
doi:10.7910/DVN/D0YLVR
Keywords: 330; party competition; challenger parties; public salience; immigration; mainstream parties